Penginjilan Pribadi Berdasarkan Yohanes 4:1-42: Sebuah Tawaran Aplikatif bagi Jemaat GPdI “Siloam” Kencong - Devi Anita Subagyo; Doni Heryanto (KHARISMATA: Jurnal Teologi Pantekosta, 2023)
This research aims to encourage the GPdI Siloam Kencong congregation to be called to be active in evangelizing missions. The lesson to be taught is taken by exposing the narrative of Jesus' conversation with the Samaritan woman in the Gospel of John. This passage is very abundant with various matters related to God's mission, including how to form and build a Biblical theology of evangelism. Yohanes presents a narrative in such depth because it touches on geography, identity, culture, polemic and so on. This is very relevant to the Indonesian context, especially for believers who have struggles to be personally involved in God's mission. This research resulted in several steps in building a biblical evangelism method. Keywords: Evangelism, Gospel of John, Jesus and the Samaritan Woman, Mission Theology